Histochemical and immunohistochemical characterization of rodlet cells in the intestine of two teleosts, Anguilla anguilla and Cyprinus carpio. Issue 3 (21st November 2017) - Bosi, G; DePasquale, J A; Manera, M; Castaldelli, G; Giari, L; Sayyaf Dezfuli, B
Abstract: Rodlet cells (RC) are characterized by a distinctive cell cortex and conspicuous inclusions named "rodlets." These cells are particularly abundant and large in size in intestine of eels. Histochemical, immunohistochemical and ultrastructural investigations were carried out on European eel Anguilla anguilla and Common carp Cyprinus carpio from Northern Italy. Eight biotinylated lectins were used to probe for specific carbohydrate residues in deparaffinized, hydrated intestinal sections of eel and carp. Five antibodies were tested on intestinal sections of both fish species: inducible nitric oxide synthase (i‐NOS), leu‐enkephalin, lysozyme, serotonin and tumour necrosis factor‐α. Lectin histochemistry revealed rodlet cells (RCs) of the eel intestine to react with two of the eight lectins tested, specifically Concanavalin A (ConA) and Sambucus Nigra Agglutinin (SNA). This contrasted to lectin staining of RCs in the intestine of common carp, where four of the eight lectins showed a positive reaction; Dolichos Biflorus Agglutinin (DBA), Wheat Germ Agglutinin (WGA), SNA and ConA. RCs in eel and carp intestine were immunoreactive with antibodies to lysozyme and i‐NOS. The occurrence of the inflammatory peptides lysozyme and i‐NOS in RCs of the eel and common carp poses in favour that these cells are involved in the mechanism of defence against pathogens.